Public acceptance and willingness to pay cost-effective taxes on red meat and road traffic in Norway - Kristine M. Grimsrud; Henrik Lindhjem; Ingvild Vestre Sem; Knut Einar Rosendahl (Statistics Norway, Research Department, 2019)
The Norwegian high-level Green Tax Commission proposes inter alia cost-effective taxes on red meat and increased toll charges on road traffic to reduce greenhouse gas emissions and local air pollution, respectively. Implementation requires support by the public, but the acceptance of such taxes is not known. We have conducted a national survey of the public's acceptance of the two taxes. The survey instrument showed dynamically the reduction in emissions/pollution for each tax level. Despite survey information about the purpose of the taxes, only 25 percent, on average, were in favour of their introduction, the rest did not know, had zero willingness to pay, or opposed the tax. In this respect, preferences for the two taxes are similar. However, on average people are willing to pay approximately 90 percent of the optimal tax for red meat, but only about 25-35 percent of toll charges on road traffic depending on fuel type. Earmarking the tax revenue for environmentally friendly technology increased acceptable tax level, but only for red meat. Earmarking tax revenues for reduced income tax did not increase the acceptable tax level.
Keywords: H23; H31; Q51; Q53; Q54; 330; Environmental taxes; red meat; road traffic; acceptance; willingness to pay